The Ugly Reflection of Philosophical and Social Variables in Postmodern Arts (The International Journal for Scientific Research, 2024)
The Ugly Consequence of Philosophical, and Social changes in Postmodern Art has had a profound impact on Art, Thought, and Culture by challenging established Beliefs, and raising questions about the nature of Reality, and Knowledge. And as a Reflection of those changes that occurred in the twentieth century, The Arts in turn rejected traditional concepts such as objective truth, absolute meaning, and classical beauty, and adopted Pluralism, Deconstruction, Uncertainty, Decentralization, Individualism, and Futility over Philosophical Thought, resulting in fragmented and chaotic Artistic Expression, and emphasised criticism and questioning traditional Beliefs and Values, resulting in Art that is often critical and controversial. Postmodern art has embraced Cultural Pluralism by attempting to blend different values to express Social Conditions, and has completely distanced itself from Abstraction. Postmodern concepts have been formulated on the basis of a critique of modernism, which was based on the idea of the existence a History of Thought that moves usually on the basis of possessing understandable Concepts as complete Origins, and in Postmodern Art we found out a return to representational language, and differentiated consistency that suits different tastes as it carries different messages, and artistic trends became more interactive with Society and the Public, which gives the Artwork the characteristic of spread and integration with the surrounding environment, whether Social, Cultural, Economic, or Political.These changes have also led to diverse Arts that are rich in experiences, but are often difficult to understand and unconventional, which have led to criticism of these arts for being elitist and chaotic, yet they have contributed to the development of new and interesting Art Forms.In conclusion, Philosophical and Social Changes have played an important role in the formation of Postmodern Art, and the emergence of many new features accompanied by some negative consequences.
Keywords: Society; Absence of a Unified Narrative of History; Lack of Absolute Truth; Cultural Pluralism; Stylistic Pluralism; Ambiguity; Uncertainty; Decentralization